Strategic Financial Planning for Long-Term Sustainability in Madrasah Aliyah - Riinawati; Fatwiah Noor; Iqbal Firdausi; Karwanto; Wahyudin (Nazhruna: Jurnal Pendidikan Islam, 2024)
This study investigates strategic financial planning for long-term sustainability in Madrasah Aliyah Siti Mariam Banjarmasin. The objective is to analyze the institution's financial challenges, explore strategies for enhancing financial sustainability, and propose recommendations for effective financial management. The research employs qualitative methods, including interviews and observations, to gather data on financial practices, challenges, and strategies within the institution. The findings reveal significant challenges in allocating financial resources effectively, including dependence on Government funding and limited investment in critical areas such as infrastructure and staff development. However, the study also identifies promising strategies for improving financial sustainability, such as diversifying revenue streams through fundraising events and partnerships, optimizing resource utilization, and implementing prudent financial management practices. Based on these findings, recommendations are proposed to prioritize investments in key areas, enhance revenue diversification efforts, and foster a culture of financial responsibility within the institution. Overall, the study contributes to understanding strategic financial planning in educational institutions and provides practical insights for enhancing long-term sustainability in Madrasah Aliyah Siti Mariam Banjarmasin.